Overcoming Barriers to Preventing and Treating P. aeruginosa Infections Using AAV Vectored Immunoprophylaxis - Jordyn A. Lopes; Amira D. Rghei; Brad Thompson; Leonardo Susta; Cezar M. Khursigara; Sarah K. Wootton (Biomedicines, 2022)
Pseudomonas aeruginosa is a bacterial pathogen of global concern and is responsible for 10–15% of nosocomial infections worldwide. This opportunistic bacterial pathogen is known to cause serious complications in immunocompromised patients and is notably the leading cause of morbidity and mortality in patients suffering from cystic fibrosis. Currently, the only line of defense against P. aeruginosa infections is antibiotic treatment. Due to the acquired and adaptive resistance mechanisms of this pathogen, the prevalence of multidrug resistant P. aeruginosa strains has increased, presenting a major problem in healthcare settings. To date, there are no approved licensed vaccines to protect against P. aeruginosa infections, prompting the urgent need alternative treatment options. An alternative to traditional vaccines is vectored immunoprophylaxis (VIP), which utilizes a safe and effective adeno-associated virus (AAV) gene therapy vector to produce sustained levels of therapeutic monoclonal antibodies (mAbs) in vivo from a single intramuscular injection. In this review, we will provide an overview of P. aeruginosa biology and key mechanisms of pathogenesis, discuss current and emerging treatment strategies for P. aeruginosa infections and highlight AAV-VIP as a promising novel therapeutic platform.